Describing Trajectories of Homeless Service Use in Hawai'i Using Latent Class Growth Analysis. Issue 1 (13th March 2017) - Gleason, Kristen; Barile, John P.; Baker, Charlene K.
Highlights: Administrative data were used to explore diverse service patterns among those new to a homeless system. The findings indicated that most individuals in the sample (85%) had very low levels of service use. A small number of individuals (about 5%) demonstrated problematic patterns of service use. Several related risk factors were identified, along with suggested programmatic solutions. The importance of considering the sociocultural context of the homeless system was also highlighted. Abstract: The State of Hawai'i, like many other areas across the United States, has large numbers of individuals and families experiencing homelessness, many of whom seek support through statewide shelters and services. This study explored the diversity of ways in which individuals and families moved through Hawai'i's homeless service system. Using administrative data, a cohort of new service users was tracked across time to trace the developmental trajectories of their homeless service use. The sample consisted of adults who had entered the service system for the first time in the fiscal year (FY) of 2010 ( N  =   4655). These individuals were then tracked through the end of FY 2014, as they used emergency shelter, transitional shelter, and outreach services. A latent class growth analysis was conducted and identified four distinct patterns of service use: low service use ( n  =   3966, 85.2%); typical transitional shelter use ( n  =   452, 9.7%); atypical transitional use ( n  =   127, 2.7%), and potential chronic service use ( n  =   110, 2.4%). Multinomial logistic regression models were then used to determine if select demographic, family, background experience (e.g., education, employment), or health variables were associated with class membership. The distinct profiles for class membership are discussed.